Structural changes in calcium silicate hydrate gel and resulting improvement in phosphate species removal properties after mechanochemical treatment. Issue 12 (12th December 2018) - Maeda, Hirotaka; Yokota, Satoshi; Kasuga, Toshihiro
Abstract : The discharge of phosphate species into aqueous environments is a key issue for eutrophication prevention. In this study, we investigate a mechanochemical treatment of calcium silicate hydrate (C-S-H) gel with different organic solvents with the aim of changing its structure and improving its phosphate species removal properties. The treatment leads to a collapse of the gel structure, resulting in the formation of defective structures in the silicate anion chains. The C-S-H gel sample milled with acetone exhibits better phosphate species recovery characteristics than does the unmilled C-S-H gel sample or the C-S-H gel sample milled with 1-propanol. Ultraviolet irradiation during phosphate recovery using the C-S-H gel sample milled with acetone further enhances the recovery properties.